2020
DOI: 10.1155/2020/4670948
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Wharton’s Jelly Stem Cell Conditioned Medium Induces Immunogenic Cell Death in Lymphoma Cells

Abstract: Mesenchymal stem cells from Wharton’s jelly of the human umbilical cord (hWJSCs), and the conditioned medium (hWJSC-CM) prepared from them, were shown to be tumoricidal on many cancers. However, these tumoricidal effects were observed in hWJSCs grown under normoxic conditions of 21% oxygen in the laboratory. Since oxygen concentrations in the stem cell niche or physiological microenvironment are hypoxic and help to maintain stemness properties, the objective of this work was to evaluate whether there were diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…With their higher accessibility, higher cell vitality, lower senescence, and fewer ethical constraints than other adult counterparts, hUCMSCs are viewed as a better choice of MSCs for clinical application [ 39 ], and banks of hUCMSCs are being set up in many countries [ 40 ], which is why we selected hUCMSCs as the source of stem cell-derived EVs. The physiological oxygen tension in the umbilical cord is about 5% [ 41 ], and similar to a previous study [ 42 ], the cell proliferation and viability of MSCs was increased at 24 h of hypoxic exposure, which might be an explanation for the more release of EVs under hypoxia. Our data revealed that hypoxia could not alter the average size of EVs.…”
Section: Discussionsupporting
confidence: 82%
“…With their higher accessibility, higher cell vitality, lower senescence, and fewer ethical constraints than other adult counterparts, hUCMSCs are viewed as a better choice of MSCs for clinical application [ 39 ], and banks of hUCMSCs are being set up in many countries [ 40 ], which is why we selected hUCMSCs as the source of stem cell-derived EVs. The physiological oxygen tension in the umbilical cord is about 5% [ 41 ], and similar to a previous study [ 42 ], the cell proliferation and viability of MSCs was increased at 24 h of hypoxic exposure, which might be an explanation for the more release of EVs under hypoxia. Our data revealed that hypoxia could not alter the average size of EVs.…”
Section: Discussionsupporting
confidence: 82%
“…[135] In 2020, the authors further found that hypoxic hWJSC-CM had greater tumor-killing ability than normoxic hWJSC-CM; therefore, new drugs against malignancy using hypoxic hWJSC-CM should be preferred (Figure 7). [136] The current method for ICD induction of lymphoma involves two modes: using ICD strategies to enhance the immune activity of DC vaccines, and using the corresponding culture medium for DC stimulation. Other studies on the induction of ICD in lymphoma cells to improve immunogenicity of apoptotic cells are ongoing, aimed at providing new diagnostic and treatment options and prolonging overall survival in patients with relapsed or refractory lymphoma.…”
Section: Lymphomasmentioning
confidence: 99%
“…C) Immunogenic cell death analysis and the secreted ATP and HMGB1 levels of lymphoma cells after treatment with normoxic and hypoxic hWJSC-CM. Reproduced under the terms of the Creative Commons CC-BY license [136]. Copyright 2020, The Authors.…”
mentioning
confidence: 99%
“…HMGB1 and calreticulin can activate DCs via toll-like receptor (TLR)-4 signaling [ 115 ]. In addition, calreticulin neutralizes CD47 receptors on the tumor cell surface, and thereby, increases the tumor cell engulfment by macrophages [ 116 ]. OV-mediated ICD, along with other ICD-inducing methods such as chemotherapy and radiotherapy, break immune tolerance against the tumor and increase lymphocyte and neutrophil infiltration, leading to antitumor response and more survival in preclinical models [ 111 ].…”
Section: Oncolytic Virus Effects On Tmementioning
confidence: 99%